KETERAMPILAN AKTIF RESEPTIF DAN PEMAHAMAN KAIDAH BAHASA INDONESIA PARA GURU SD SEKOTA PONTIANAK - NFN Irmayani (Balai Bahasa Kalimantan Barat, 2020)
This paper aims to describe the language skills of Indonesian language mastered by the elementary school teachers in Pontianak based on the linguistic component in the language test. The skill level was based on the result of UKBI Training Series conducted for elementary school teachers in 2018. The descriptive method is used to present the results of data analysis. Based on the results of the discussion, it was found that the Indonesian language skill of the elementary school teachers in Pontianak was at the level of Very Advanced, Advanced, Upper Intermediate, Intermediate and Elementary. The majority of these teachers were at the Upper Intermediate level, while the minority was at the Elementary level. In addition, it was also found that the elementary school teachers in Pontianak City got the highest score in the section of Understanding the Reading. In contrast, teachers who were graded Very Advanced got the highest score on the section of Responding the Grammar. However, in contrast to the highest score on the linguistic component, most elementary school teachers in Pontianak got the highest score in the section of Understanding the Reading. This can be seen from the frequency of high scores for that section at every rank.